2016
DOI: 10.1007/s10926-016-9664-z
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Interventions to Prevent Disability from Both the Scientific and Practice Perspectives: A Comparison of Scientific Literature, Grey Literature and Stakeholder Observations

Abstract: Purpose The significant individual and societal burden of work disability could be reduced if supportive workplace strategies could be added to evidence-based clinical treatment and rehabilitation to improve return-to-work (RTW) and other disability outcomes. The goal of this article is to summarize existing research on workplace interventions to prevent disability, relate these to employer disability management practices, and recommend future research priorities. Methods The authors participated in a year-lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 69 publications
1
33
0
2
Order By: Relevance
“…It was suggested that employers may play an essential role for work participation of cancer survivors, with supervisor support being an important RTW facilitator . The importance of employer support for work participation of cancer survivors was also perceived by both employers and survivors in the current review.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was suggested that employers may play an essential role for work participation of cancer survivors, with supervisor support being an important RTW facilitator . The importance of employer support for work participation of cancer survivors was also perceived by both employers and survivors in the current review.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of stakeholders upon RTW of cancer survivors varies among different countries (eg, because of differences in legislation), many studies across different countries acknowledge employers as one of the most important stakeholders during the RTW of cancer survivors . Employers are in the position to guide cancer survivors back to work and create good working conditions .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations